Aplikasi Terapi Digital Anak Penyandang Autism di Komunitas Forkesi Chapter Surabaya - Mahmudah, Hani'ah; Pratiarso, Aries; Saleh, Akuwan; Yuliana, Mike; Kristalina, Prima; Samsono Hadi, Moch. Zen; Dutono, Titon; Anisah, Ida; Sa’adah, Nihayatus (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2022)
Many parents in the Surabaya Chapter Forkesi Community (Indonesian Special Children's Parents Communication Forum) do not understand how to care for and teach children with autism, despite the fact that 50 percent of the members of this community are parents of children with autism. This service aims to assist parents in dealing with their autistic children on a daily basis. Furthermore, to address the issue of disadvantaged children with autism who are unable to participate in therapy or seek treatment from psychologists on a regular basis due to the high expense of doing so. The development of an augmented reality-based android mobile application using the marker method will include learning materials for build a match and WH questions, as well as games to help deepen learning, and will be used in conjunction with the ABA method and DTT technique. In May-July 2021, this service activity was carried out in the Surabaya Chapter Forkesi community. Data collecting, interactions with community members, and direct implementation were the strategies used in this service. According to the findings of the Usability Testing, which received a score of 54.6, parents of children with autism agree on the use of digital therapy via Android mobile app.